STRUKTUR KOMUNITAS DAN PERSENTASE TUTUPAN LAMUN DI MARINE FIELD STATION UNIVERSITAS SAM RATULANGI - Anastasia V Senduk; Joshian N W Schaduw; Veibe Warouw; Billy Th. Wagey; Joice RTSL Rimper; Anneke V Lohoo (Sam Ratulangi University, 2021)
In the world there are 60 species of seagrass, and 12 types are found in Indonesia. This study aims to determine the results of the description of the community structure and the percentage cover of seagrass in the waters of the Marine Fields Station, observations were made at 2 (ST.1 & ST.2) stations using themethod seagrass watch and the results of data analysis of the community structure using the equation formula from Cox, 1967. In the waters of the Marine Fields Station, there are 6 species, namely Enhalus acoroides, Thalassia hemprichii, Cymodocea rotundata, Syringodium isoetifolium, Halodule pinifolia, and Halophile ovalis. The results of the percentage of seagrass cover at ST.1 were 58.85% and ST.2 53.13% and the average value obtained from these 2 stations was 55.99%. Overall, the community structure of ST.1 species Thalassia hemprichii has the highest important value index of 80.66%. And in ST.2 Syringodium isoetifolium which has the highest important value index is 93.27%. Parameters in the waters of Maine Field Station, namely pH, salinity, temperature, substrate are good.Â Keywords: Seagrass, Percentage Cover, Community StructureÂ